2021
DOI: 10.35631/ijmtss.416001
|View full text |Cite
|
Sign up to set email alerts
|

Acceptance of Good Agricultural Practices (Gap) Among Independent Oil Palm Smallholders in Malaysia

Abstract: Several oil palm sustainable certification schemes have been introduced in Malaysia such as MPOB Codes of Good Agricultural Practices (MPOB CoGAP) Certification, Roundtable on Sustainable Palm Oil (RSPO) certification, and Malaysia Sustainable Palm Oil (MSPO) Certification. All these certifications have been successfully accepted in many of the oil palm estates except the ISH. There is a big challenge to certify the Malaysian ISH because they are lack farm management practice. Therefore, Malaysian Palm Oil Bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Palm oil GAP in Malaysia is the basis for increasing productivity and is a requirement for MSPO [23]. Although GAP through MSPO promotes increased productivity, the effectiveness of GAP in delivering the well-being of smallholders in FFB production areas still needs to be determined.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Palm oil GAP in Malaysia is the basis for increasing productivity and is a requirement for MSPO [23]. Although GAP through MSPO promotes increased productivity, the effectiveness of GAP in delivering the well-being of smallholders in FFB production areas still needs to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, they will receive wages monthly even if there is no production that month. On the other hand, compared to organised smallholders, the farm management of ISHs is poor because, according to Mansor (as cited in [23]), from 400 ISH, only 26% apply GAP.…”
Section: Hypothesis 2 (H2) Productivity Has a Positive Correlation Wi...mentioning
confidence: 99%
See 1 more Smart Citation
“…The implementation of Good Agriculture Practice (GAP) is also considered as the baseline for the MSPO certification. Mansor et al (2021) revealed that 58% of the ISH partially complied with GAP requirements. Whereas, only 26% of ISH fulfilled the requirements, and thus, were eligible for the GAP certification.…”
Section: Sustainable Development For Smallholdersmentioning
confidence: 95%
“…Labour shortage has also impacted yields among the ISH, albeit at a smaller scale as compared to the plantations. According to Nazirah et al (2021), the majority of oil palm ISH were not entirely reliant on foreign workers to carry out activities in their smallholdings. The study provide an insight which showed that ISH hired 21.8% of foreign workers for harvesting, 19.8% for weed control, and 16.8% for fertiliser application.…”
Section: Sustainable Development For Smallholdersmentioning
confidence: 99%